Pancasila as State Ideology and Pillar of Religious Harmony in Indonesian Society - Nurdianzah, Erry; Azizah, Nurul; Rahmawati, Riza; Munib, Ahmad; Sulistyowati, Octalia Heri; Albary, Hanifah (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
Religious diversity in a country is natural, but even so, an arrangement within the country is needed to accommodate differences in religion and belief. Without a fair arrangement, this can make the state less stable and cause religious conflicts in a country.This article examines Pancasila as the state ideology in forming religious tolerance. This research is a qualitative research with a literature study approach, namely by using books, documents, journals and other related sources as sources of research data. This study discussed about Pancasila as state ideology and religion, Pancasila Philosophy in Islamic Views, and Pancasila as an ideology forming religious tolerance. While data analysis is carried out by grouping, sorting and then looking for themes that are in accordance with the focus of research for later interpretation. Results of studi show;1) Pancasila as the state ideology has been fully supported by religious normativity. 2) The values and norms contained in Pancasila have compatibility with the values that become the teachings of Islam. and 3) Pancasila plays an important role in creating religious tolerance, mutual respect and respect for adherents of other religions, and not forcing beliefs on other parties.